Lamborghini's affair: Osvaldo Lamborghini´s circulation in Babel magazine (1988-1991) - Conde de Boeck, José Agustín (2018)
Osvaldo Lamborghini was a key author in the construction of 70’s and 80’s Argentine literary canon. Creator of an atypical work and a strong system of sexual and political symbolism, his influence was fundamental to next generations, which identified his aesthetical transgression with the possibility of an alternative literature against Borges’ “high cultural” standards. In the late 80’s, Babel magazine, composed of young emerging authors of that time, perceived in Lamborghini’s work an emblem for the magazine’s own proposals, particularly with regard to the debates about the turn from a “modern” literature to a “postmodern” one. In connection with “canon” and “postmodernity” concepts, we will study here the ways in which Babel, main organ in the postdictatorship literary journalism, appropriated Osvaldo Lamborghini’s image in order to turn it into the axis of debates and tensions circulating in 80’s Argentine literary field. We consider that the analysis of cultural legitimation operated in the “babelic” rereading of Lamborghini could offer a key to understanding the formation of Argentine literary canon in the last decades.